Application of digital marketing as strategy marketing MSMEs - Suwianto, Suwianto; Tarigan, Purnaya Sari; Pelawi, Pioner; Tulim, Anto (Junal Ilmu Manajemen, 2024)
Development Internet technology marking the beginning of the Revolutionary era Industry 4.0. The presence of the Internet provides access information in a way fast and easy become method new for MSMEs in promote the product, because the Internet has change principle base marketing from the traditional world become digital marketing. The objective of this study is to know impact digital marketing against sales, strategy marketing and barriers adoption digital marketing in MSMEs. This study use method qualitative. The study began with a series of qualitative interviews that identified relationships that required further investigation. The interview was conducted by one person who is an MSME actor or owner of AnyaOlshop. This study found that MSMEs that implement digital marketing achieve higher sales. Therefore, MSME players are more satisfied if they sell their products online. The strategy for implementing digital marketing to sell products is to use social media such as Facebook, Instagram, WhatsApp status, live streaming on Facebook. The results also show that although there are benefits to be gained from implementing digital marketing, MSMEs face many obstacles in implementing it. These failures include unstable internet connections, delivery delays, even fraudulent transactions and manipulation of admin numbers. The application of digital marketing influences the increase in MSME marketing and it can be concluded that the application of digital marketing brings related benefits and obstacles.